Small Convenience Stores and the Local Food Environment: An Analysis of Resident Shopping Behavior Using Multilevel Modeling. Issue 3 (January 2016) - Ruff, Ryan Richard; Akhund, Ali; Adjoian, Tamar
Purpose: Local food environments can influence the diet and health of individuals through food availability, proximity to retail stores, pricing, and promotion. This study focused on how small convenience stores, known in New York City as bodegas, influence resident shopping behavior and the food environment. Design: Using a cross-sectional design, 171 bodegas and 2118 shoppers were sampled. Setting: Small convenience stores in New York City. Subjects: Any bodega shopper aged 18+ who purchased food or beverage from a participating store. Measures: Data collection consisted of a store assessment, a health and behavior survey given to exiting customers, and a bag check that recorded product information for all customer purchases. Analysis: Descriptive statistics were generated for bodega store characteristics, shopper demographics, and purchase behavior. Multilevel models were used to assess the influence of product availability, placement, and advertising on consumer purchases of sugar-sweetened beverages (SSBs), water, and fruits and vegetables. Results: Seventy-one percent of participants reported shopping at bodegas five or more times per week, and 35% reported purchasing all or most of their monthly food allotment at bodegas. Model results indicated that lower amounts of available fresh produce were significantly and independently associated with a higher likelihood of SSB purchases. A second, stratified multilevel model showed that the likelihood of purchasing an SSB increased with decreasing varieties of produce when produce was located at the front of the store. No significant effects were found for water placement and beverage advertising. Conclusions: Small convenience stores in New York City are an easily accessible source of foods and beverages. Bodegas may be suitable for interventions designed to improve food choice and diet.